1999
DOI: 10.1152/ajpcell.1999.276.4.c821
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of oligopeptide transporter Pept-1 in a human intestinal cell line

Abstract: The intestinal oligopeptide transporter (cloned as Pept-1) has major roles in protein nutrition and drug therapy. A key unstudied question is whether expression of Pept-1 is hormonally regulated. In this experiment, we investigated whether insulin has such a role. We used a human intestinal cell monolayer (Caco-2) as the in vitro model of human small intestine and glycylglutamine (Gly-Gln) as the model substrate for Pept-1. Results showed that addition of insulin at a physiological concentration (5 nM) to incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(93 citation statements)
references
References 18 publications
5
86
0
2
Order By: Relevance
“…It is also unclear how hormonal or neural pathways affect oligopeptide regulation in the developing intestine and kidney. These factors were beyond the scope of the present study, but may be important as suggested previously (11,20,34).…”
mentioning
confidence: 72%
“…It is also unclear how hormonal or neural pathways affect oligopeptide regulation in the developing intestine and kidney. These factors were beyond the scope of the present study, but may be important as suggested previously (11,20,34).…”
mentioning
confidence: 72%
“…In this regard, the role of insulin in the regulation of a number of intestinal epithelial processes is well established. For example, insulin has been shown to stimulate the function of oligopeptide transporter, Pept-1 (36), to decrease the transepithelial resistance (28), and to abrogate calcium-dependent chloride secretion in T84 intestinal epithelial cells (8). Additionally, previous studies have shown that insulin acutely decreased glucose flux across rat jejunum and ileum (27).…”
Section: G903 High Bile Acid Absorption In Stz-induced Diabetes Mellitusmentioning
confidence: 99%
“…In Caco-2 cells, insulin (65), leptin (15), 1 -and ␣ 2 -adrenergic receptor ligands such as (ϩ)pentazocine (26), and clonidine (9) all were shown to stimulate uptake of dipeptides or ␤-lactams via PEPT1. On the other hand, either exposure to two immunosuppressive agents, tacrolimus and cyclosporin A (44), or exposure to thyroid hormone (5) or long-term basolateral stimulation with EGF inhibited the uptake of dipeptides via PEPT1 in Caco-2 cells (44).…”
Section: Regulation Of Expression Level and Transport Activity Of Pepmentioning
confidence: 99%